Impact of parasitic infection with Ascaris lumbricoides on pulmonary function tests in asthmatic and non-asthmatic children - Suha Haithem Mohammed (Elsevier, 2021)
Background: There is strong evidence for a causal relationship between helminthes infection and allergic disease like asthma due to the similarity in the way they respond. This study aimed to investigate the effects of Ascaris infection on pulmonary function tests (PFTs) to reveal the relationship between ascariasis and asthma in children. Patients and methods: This a randomized-control study conducted in Basrah City, Iraq, in which four groups of a total of 490 children were enrolled: Group1 included 120 normal children; Group 2 included 135 asthmatic children; Group 3 who were 150 Ascaris infected children and group G4 included 85 asthmatic and Ascaris infected. PFTs, IgE level, differential blood count and parasitic examination were done for all groups. Results: Both group2 and 4, which included asthmatic children showed a significant decrease in PFT (P > 0.05),while the PFT of parasitic infected group was not affected. There were no significant changes in WBC, eosinophils and IgE between asthmatic and parasitic infected groups. Conclusion: Ascaris infection could induce the inflammatory immune response in children, but couldn't cause a significant effect on pulmonary function tests in these children; The impairment in PFT was due to asthma disease and not correlated to ascariasis.